About the Consideration of the Inactive Materials and the Meshing Procedures in Computational Models of Lithium Ion Battery Electrodes - Dr. Mehdi Chouchane; Prof. Dr. Alejandro A. Franco (ChemElectroChem, 2022)
Abstract Lithium‐ion batteries (LIBs) constitute a crucial technology in the ongoing energy transition. Still, the composite porous electrodes in LIBs remain complex systems which still need optimization to meet the requirements from the applications, e. g., high energy density for the automotive sector. To achieve well‐designed LIB electrodes, computational continuum modeling with three‐dimensional (3D) resolution constitutes a powerful tool to gain insights on the working principles of these electrodes. However, due to the complexity of the material properties and geometrical features within the electrodes, until mid‐2010’s such type of models had to make numerous assumptions, especially regarding the carbon additive and binder (all together standing for the so called inactive phase), that was not explicitly resolved in 3D. Recently, the battery modeling field has undergone tremendous progress which allowed the emergence of a new generation of models, more accurate and realistic than ever before. This review presents the latest developments through the prism of the consideration of the inactive phase in these models, and also provides recommendations on how to design modeling studies in order to minimize numerical errors originated by the meshing procedures of the materials and electrode volumes, a crucial step when a continuum model is set.